Temporary Gasserian ganglion stimulation utilizing SNM electrode in subacute herpetic trigeminal neuralgia - Niu, Jiejie; Wang, Chenhui; Wang, Xing; Lu, Guijun (Frontiers in Neurology, 2024)
Objective Gasserian ganglion stimulation (GGS) is a neuromodulation technique that has been extensively applied in treating postherpetic trigeminal neuralgia. However, permanent implantation of GGS was preferred in most treatment approaches. Few studies have investigated temporary GGS for the treatment of acute/subacute herpetic trigeminal neuralgia. Moreover, previous research has reported lead dislocation when utilizing traditional electrodes, which was associated with poor pain relief. In GGS research, preventing the accidental displacement of lead following implantation has consistently been a primary objective. Methods We report a case of a 70-year-old woman with subacute herpetic trigeminal neuralgia who underwent temporary GGS for 14 days utilizing a sacral neuromodulation (SNM) quadripolar-tined lead. Computed tomography-guided percutaneous foramen ovale (FO) puncture and temporary SNM electrode implantation were performed during the surgery. A telephone interview was conducted to record a 12-month follow-up. Results At admission, zoster-related trigeminal pain severity was assessed to be 9/10 on the visual analog scale (VAS). After a 14-day GGS treatment, the pain assessed on the VAS score reduced to 1/10 at discharge but increased to 4/10 at the 12-month follow-up after surgery. Additionally, the anxiety level improved from 58 points to 35 points on the Self-Rating Anxiety Scale (SAS), and the depression level improved from 62 points to 40 points on the Self-Rating Depression Scale (SDS). The Physical Component Summary score of the 12-item Short-Form Health Survey (SF-12) increased from 33.9 to 47.0, and the Mental Component Summary (MCS) score of the SF-12 increased from 27.4 to 41.9. Conclusion Temporary GGS might be a potentially effective treatment for subacute herpetic trigeminal neuralgia, and an SNM electrode might be a good choice for reducing the risk of dislocation.